Response to Jim Tucker - Sudduth, Michael (Journal of Scientific Exploration, 2022)
Let me begin by thanking Jim Tucker for offering his thoughts on my JSE paper on the James Leininger case (Sudduth 2021). I appreciate his clarifying his interpretation of several of the facts in the case, as well as his providing further context to some of them. I also appreciate his acknowledgement of Bruce Leininger’s authorship of the 2003 chronology which I uncovered in my investigation and made use of in my paper. That’s all helpful. For the rest, I wish I could say what St. Augustine said to Evodius when responding to the latter’s criticisms – “you have knocked vigorously.” Alas, I cannot say this about Tucker’s response. My paper developed a number of different concerns about the evidential value of the James Leininger case (hereafter, JL case). The paper was lengthy and the scope of the material I presented was broad, often involving considerable detail regarding different aspects of the case. I realize this can make writing a concise and salient response a daunting task. To effectively navigate the landscape, therefore, it’s crucial to properly understand the structure and content of my arguments, as well as how I intend to leverage various facts in the service of specific lines of argument. One must not miss the forest (the argument) for the trees (particular facts). Or, in the words of St. Augustine, one must knock vigorously. Tucker has not.